STUDY OF THE PROCESS OF DECOMPOSITION OF DOLOMITE "SHORSU" WITH NITRIC ACID TO OBTAIN A SOLUTION OF CALCIUM AND MAGNESIUM NITRATES - Saydullayeva G.A (Western European Studies, 2025)
This article examines the possibility of obtaining a solution of calcium and magnesium nitrates by decomposing dolomite m.r. "Shorsu" with nitric acid. The process of decomposition of dolomite with nitric acid was studied depending on the concentration of the acid and temperature.
Keywords: dolomite; nitric acid; solution of calcium and magnesium nitrates